2019
DOI: 10.3390/cancers11121858
|View full text |Cite
|
Sign up to set email alerts
|

FoxO3a as a Positive Prognostic Marker and a Therapeutic Target in Tamoxifen-Resistant Breast Cancer

Abstract: Background: Resistance to endocrine treatments is a major clinical challenge in the management of estrogen receptor positive breast cancers. Although multiple mechanisms leading to endocrine resistance have been proposed, the poor outcome of this subgroup of patients demands additional studies. Methods: FoxO3a involvement in the acquisition and reversion of tamoxifen resistance was assessed in vitro in three parental ER+ breast cancer cells, MCF-7, T47D and ZR-75-1, in the deriving Tamoxifen resistant models (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 59 publications
(84 reference statements)
4
37
0
Order By: Relevance
“…Cells were plated in GM for 24 h and, after 1 h MSNs treatment, shifted to fresh GM medium. After 36 h, cells were lysed as previously described [ 65 ]. Briefly, harvested cells were incubated (10 min on ice) with cytoplasmic buffer containing 1 M sucrose, 1 M Hepes, 1 M KCl, 1 M MgCl2, 1 M EDTA, 1 M EGTA, Digitonin 10% and 200 mM PMSF.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were plated in GM for 24 h and, after 1 h MSNs treatment, shifted to fresh GM medium. After 36 h, cells were lysed as previously described [ 65 ]. Briefly, harvested cells were incubated (10 min on ice) with cytoplasmic buffer containing 1 M sucrose, 1 M Hepes, 1 M KCl, 1 M MgCl2, 1 M EDTA, 1 M EGTA, Digitonin 10% and 200 mM PMSF.…”
Section: Methodsmentioning
confidence: 99%
“…FOXO3a inhibition leads to breast cancer carcinogenesis [ 132 ]. FOXO3a overexpression is a desirable factor for prognosis, and its downregulation occurs in drug-resistant breast cancer cells [ 133 ]. Increasing evidence demonstrates that FOXO3a is a down-stream target of Akt [ 134 , 135 , 136 ].…”
Section: Microrna and Pten Relationshipmentioning
confidence: 99%
“…Bioinformatic analysis indicated that circ_0025202 may act as a miRNA sponge. Further experiments proved that circ_0025202 can upregulate FOXO3a, an inhibitor of TAM resistance in BC [ 173 ], by sponging miR-182-5p, leading to reversion of TAM resistance. Liang et al [ 174 ] identified a novel circRNA, circBMPR2, as a suppressor of TAM resistance in BC.…”
Section: Endocrine Drugsmentioning
confidence: 99%